A novel evaluation regarding the influence of surface emissivity on radiative and total heat transfer coefficients in radiant heating systems by means of theoretical and numerical methods - Acikgoz, Ozgen (ELSEVIER SCIENCE SA, 2015)
In the present study, we investigate by means of theoretical calculations and the program Engineering Equation Solver (EES) total and radiative heat transfer coefficients in an enclosure heated from its one wall at several surface emissivities (epsilon = 0.90, 0.85, 0.80), with room dimensions (L x H x W=1.8 x 2.85 x 1.8, 3 x 2.85 x 3, 3 x 2.85 x 4, 4 x 2.85 x 3, 6 x 2.85 x 6 m) and surface temperatures (T-h =20-40 degrees C, T-c = 5-15 degrees C, T-f=14-31 degrees C and T-ceil = 10-27 degrees C). To understand the influence of convection through computational methods in the aforementioned conditions, we performed numerical procedures and found a correlation including the aspect ratio influence (H/L). Afterward, through the tables and figures, we show that the average radiative coefficient lies within the range of 5.4-5.5 W/m(2) K and varies very slightly with room dimensions and temperature differences at practical applications at the surface emissivity value of 0.9, which is a close value to a surface emissivity practically. Furthermore, we found the total heat transfer coefficient to be between 10.2 and 10.8 W/m(2) K for the emissivity value of 0.9, and we observed that it did not significantly vary with room dimensions. Additionally, similar to the experimental literature results, we found that the average proportion of radiation to the total heat transfer was between 64% and 67%. (c) 2015 Elsevier B.V. All rights reserved.
Keywords: Radiation; Radiative heat transfer coefficient; Total heat transfer coefficient; Convective heat transfer coefficient; Heat transfer; Enclosures; Radiant heating systems; INTERNAL BUILDING SURFACES; FLOOR NUSSELT NUMBER; NATURAL-CONVECTION; THERMAL PERFORMANCE; APPROACH RELEVANT; ROOM SURFACES; WALL; Construction & Building Technology; Energy & Fuels; Engineering